Natural infection of Aedes aegypti, Ae. albopictus and Culex spp. with Zika virus in Medellin, Colombia - Pérez-Pérez, Juliana; Rojo-Ospina, Raul; Henao-Correa, Enrique; García-Huertas, Paola; Triana-Chavez, Omar; Rúa-Uribe, Guillermo L. (CES Medicina, 2019)
Introduction: The Zika virus has generated serious epidemics in the different countries where it has been reported and Colombia has not been the exception. Although in these epidemics Aedes aegypti traditionally has been the primary vector, other species could also be involved in the transmission. Methods: Mosquitoes were captured with entomological aspirators on a monthly basis between March and September of 2017, in four houses around each of the 250 entomological surveillance traps installed by the Secretaria de Salud de Medellin (Colombia). Additionally, 70 Educational Institutions and 30 Health Centers were visited each month. Results: 2 504 mosquitoes were captured and grouped into 1045 pools to be analyzed by RT-PCR for the detection of Zika virus. Twenty-six pools of Aedes aegypti, two pools of Ae. albopictus and one for Culex quinquefasciatus were positive for Zika virus. Conclusion: The presence of this virus in the three species and the abundance of these species in the different sectors of the city, suggests that the control strategies should be addressed to all species that could be potential vectors until the vectorial role of Ae. albopictus and Culex quinquefasciatus is completely elucidated in the transmission of the Zika virus.